Sound symbolism in the Proto-Turkic language - Khassenov, Bolat (Penerbit Universiti Kebangsaan Malaysia, 2021)
Studies on the Turkic languages have shown that the difference between related terms concerning male and female, including back and front vowels, is a “separate case” (a special case). In this article, such a phenomenon was studied in more depth and detail, and for the first time, it was associated with sound symbolism. This work aims to show the role of sound symbolism in the classification of kinship terms related to man and woman in the Proto-Turkic language. To achieve this goal, we conducted experimental work with four babies. Our experiment was based on the bouba/kiki effect, which is used in modern linguistics. Besides, in the research work, an associative experiment was conducted with students studying at Karaganda University. Thirty-five students took part in the experiment. The study results showed that infants associated the image of a man, large objects with back vowels, and the image of a woman, small objects with front vowels. According to the results obtained using the associative method, the participants associated the front vowels with the stimulus “female”, and the back vowels were not associated with “male”. However, the participants showed an advantage in associating men with the uvular consonant [q], which is only combined with back vowels. In the Turkic languages, we also found that terms associated with back (thick) vowels have meanings associated with males, and terms associated with front (thin) vowels have meanings associated with females.